2020
DOI: 10.1088/1361-6560/abc364
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of noise and background signals in a magnetic particle imaging system

Abstract: Magnetic particle imaging (MPI) is a novel technology, which opens new possibilities for promising biomedical applications. MPI uses magnetic fields to generate a specific response from magnetic nanoparticles (MNPs), to determine their spatial location non-invasively and without using ionizing radiation. One open challenge of MPI is to achieve further improvements in terms of sensitivity to translate the currently preclinical performed research into clinical applications. In this work, we study the noise and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…Consistent with other imaging methods, the imaging quality of MPI is affected by background signals, which may originate from the thermal process of the scanner electronics, such as the amplifier, filter, coils, or the contamination of ferromagnetic tracers [ 67 , 68 ]. The standard measurement method of the background is measuring the SM and system response separately without the tracer, and then subtracting the background signal from the system response measured with the tracer.…”
Section: Current Sm-based Mpi Reconstruction Methodsmentioning
confidence: 99%
“…Consistent with other imaging methods, the imaging quality of MPI is affected by background signals, which may originate from the thermal process of the scanner electronics, such as the amplifier, filter, coils, or the contamination of ferromagnetic tracers [ 67 , 68 ]. The standard measurement method of the background is measuring the SM and system response separately without the tracer, and then subtracting the background signal from the system response measured with the tracer.…”
Section: Current Sm-based Mpi Reconstruction Methodsmentioning
confidence: 99%
“…44,233 In terms of instrumentation, advancements in sensitivity have most frequently been from developments in coil design. 37,74,78,79,234,235 Regarding tracer development for enhanced sensitivity, the signal intensity is governed by the physical and inherent magnetic properties of the tracer, as with spatial resolution, but is mostly dependent on the Ms. 16,18,55 Although the detection sensitivity of MPI is strong currently, through significant advancement it has the potential to become comparable with that of exceptionally sensitive nuclear imaging techniques. 234 Given what has been discussed, the development of SPIONs with optimal sensitivity and spatial resolution performance has become a crucial part of MPI research.…”
Section: Effect Of Spions On Spatial Resolution and Sensitivity In Mpimentioning
confidence: 99%
“…[378][379][380] Despite these obstacles, there has been sustained work on the translation and hardware scale-up. 42,43,79,235,381,382 In the design of a functional MPI brain imager, Mason et al developed simulation studies that demonstrated promising capabilities for human-scale systems. 383 In an alternative approach Graeser et al successfully presented a human-sized MPI hardware set-up, tailored for brain applications, that has low technical requirements for fast and flexible operation in a clinical environment.…”
Section: Clinical Translationmentioning
confidence: 99%
“…Noise in MPI systems originates from resistive components (thermal noise) and varies as a function of the sampled frequency component [34]. Thus, the additive noise in Eq.…”
Section: Signal Modelmentioning
confidence: 99%
“…Thus, the additive noise in Eq. ( 2) can be taken as colored Gaussian [34,35], where the standard deviation depends on the traversed trajectory and gradient strengths. It is common to pre-measure noise levels during background measurements, and perform noise whitening [33,[35][36][37].…”
Section: Signal Modelmentioning
confidence: 99%